2020
DOI: 10.1186/s12866-020-01968-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of the Prevotella genus within the human gut microbiota of elderly volunteers determines the inter-individual responses to dietary supplementation with wheat bran arabinoxylan-oligosaccharides

Abstract: Background The human colon is colonised by a dense microbial community whose species composition and metabolism are linked to health and disease. The main energy sources for colonic bacteria are dietary polysaccharides and oligosaccharides. These play a major role in modulating gut microbial composition and metabolism, which in turn can impact on health outcomes. Results We investigated the influence of wheat bran arabinoxylan oligosaccharides (AXOS) and maltodextrin supplements in modulating the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…This can be the result of cross-feeding reactions between bifidobacteria- and butyrate-producing WBAX responding to Faecalibacterium and Lachnospiraceae taxa ( 23 , 64 ). In CM 1, WBAX promoted propionate production and the growth of Prevotella , which corresponds with a recent study in healthy elderly that identified the Prevotella genus as a driving factor in microbiota response to wheat bran AX ( 65 ). The bloom of Prevotella also explained the succinate accumulation especially observed in native WBAX in CM 1, as some Prevotella species appear to produce succinate preferentially over propionate ( 66 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This can be the result of cross-feeding reactions between bifidobacteria- and butyrate-producing WBAX responding to Faecalibacterium and Lachnospiraceae taxa ( 23 , 64 ). In CM 1, WBAX promoted propionate production and the growth of Prevotella , which corresponds with a recent study in healthy elderly that identified the Prevotella genus as a driving factor in microbiota response to wheat bran AX ( 65 ). The bloom of Prevotella also explained the succinate accumulation especially observed in native WBAX in CM 1, as some Prevotella species appear to produce succinate preferentially over propionate ( 66 ).…”
Section: Discussionsupporting
confidence: 88%
“…Several other in vitro studies with other types of wheat bran or AX extracts observed this individual microbiota response as well ( 26 , 69 , 72 ). In addition, data from human intervention studies often show very individual responses in microbiota change upon AX supplementation ( 24 , 65 ), and their outcome is hard to predict due to the complex cross-feeding and ecological interactions occurring within the microbiota. The current setup is, therefore, a first step in gaining knowledge on the impact of processing-induced changes in soluble AX on fermentation kinetics and affected bacterial taxa but, obviously, there is a need for further investigation and validation with more individual microbiota in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known and has recently been confirmed that the gut microbiota is highly individual-specific [32]. This interindividual difference may also be the reason why a dietary intervention may show an effect or not [33]. We studied the differences in β-diversity between individuals (Figure 4a) in more detail and, when studying the first two principal coordinate axes, we observed that the differences in β-diversity between the samples were either large (usually the consequence of a single intervention; Figure 4b) or very small (Figure 4c).…”
Section: Resultsmentioning
confidence: 97%
“…For example, Chung et al . 158 recently demonstrated that supplementation with wheat bran arabinoxylan oligosaccharides in healthy adults induced variable microbiome changes dependent on the baseline relative abundance of Prevotella . In a different study, Baxter et al .…”
Section: Future Directions: From Diagnosis To Personalizationmentioning
confidence: 99%